Dun and Bradstreet Guide to - Dunnan, Nancy (HarperPerennial, etc., 1995)
An annual guide lists timely assessments and current rates, identifying today's hottest investment vehicles and offering advice on buying and selling stocks, mutual funds, IRAs, bonds, and more.